The dnd operon for DNA phosphorothioation modification system in Escherichia coli is located in diverse genomic islands - Chew Chieng, Yeo; Wing Sze, Ho; Hong-Yu, Ou (2015)
Background: Strains of Escherichia coli that are non-typeable by pulsed-field gel electrophoresis (PFGE) due to in-gel degradation can influence their molecular epidemiological data. The DNA degradation phenotype (Dnd+) is mediated by the dnd operon that encode enzymes catalyzing the phosphorothioation of DNA, rendering the modified DNA susceptible to oxidative cleavage during a PFGE run. In this study, a PCR assay was developed to detect the presence of the dnd operon in Dnd+ E. coli strains and to improve their typeability. Investigations into the genetic environments of the dnd operon in various E. coli strains led to the discovery that the dnd operon is harboured in various diverse genomic islands. Results: The dndBCDE genes (dnd operon) were detected in all Dnd+ E. coli strains by PCR. The addition of thiourea improved the typeability of Dnd+ E. coli strains to 100% using PFGE and the Dnd+ phenotype can be observed in both clonal and genetically diverse E. coli strains. Genomic analysis of 101 dnd operons from genome sequences of Enterobacteriaceae revealed that the dnd operons of the same bacterial species were generally clustered together in the phylogenetic tree. Further analysis of dnd operons of 52 E. coli genomes together with their respective immediate genetic environments revealed a total of 7 types of genetic organizations, all of which were found to be associated with genomic islands designated dnd-encoding GIs. The dnd-encoding GIs displayed mosaic structure and the genomic context of the 7 islands (with 1 representative genome from each type of genetic organization) were also highly variable, suggesting multiple recombination events. This is also the first report where two dnd operons were found within a strain although the biological implication is unknown. Surprisingly, dnd operons were frequently found in pathogenic E.coli although their link with virulence has not been explored. Conclusion: Genomic islands likely play an important role in facilitating the horizontal gene transfer of the dnd operons in E. coli with 7 different types of islands discovered so far.